1977
DOI: 10.1021/bi00644a035
|View full text |Cite
|
Sign up to set email alerts
|

Separation and characterization of microtubule proteins from calf brain

Abstract: Electrophoresis of microtubule preparations purified from calf brain by repeated cycles of assembly and disassembly shows that they contain many proteins in addition to alpha- and beta-tubulin. These additional proteins constitute about 17% of the total material present after five cycles of assembly and disassembly. Both one-dimensional and two-dimensional (P.H. O'Farrell (1975), J. Biol. Chem. 250, 4007) electrophoretic techniques have been used to characterize them. They can be divided into two groups: one t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
128
0

Year Published

1981
1981
1994
1994

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(140 citation statements)
references
References 55 publications
12
128
0
Order By: Relevance
“…In addition to this evidence for intracellular association between microtubules and neurofilaments, there is evidence of association in vitro. Neurofilaments adhere to microtubules and cosediment with them under the conditions employed in microtubule preparation (14)(15)(16). These considerations prompted the deliberate search, reported here, for a microtubule-neurofilament complex.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…In addition to this evidence for intracellular association between microtubules and neurofilaments, there is evidence of association in vitro. Neurofilaments adhere to microtubules and cosediment with them under the conditions employed in microtubule preparation (14)(15)(16). These considerations prompted the deliberate search, reported here, for a microtubule-neurofilament complex.…”
mentioning
confidence: 94%
“…Neurofilaments were prepared from bovine brain as described (17). Microtubule protein referred to as "threetimes-cycled" was prepared by three cycles of the assembly/ disassembly method of Shelanski and coworkers (14,18). Phosphocellulose (PC)-purified tubulin was prepared from twicecycled microtubule protein (19,20).…”
mentioning
confidence: 99%
“…When such preparations are visualized with the electron microscope, MAP2 appears as regularly spaced filamentous sidearms decorating the surface of microtubules (1), reminiscent of the appearance of microtubules in situ (4,5). In addition to its interaction with microtubules, MAP2 interacts with neurofilaments and actin filaments (3,(6)(7)(8)(9)(10). This suggests that MAP2 may act as a crosslinker mediating the interaction between microtubules, other cytoskeletal elements, and cytoplasmic organelles.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of a number of high molecular weight polypeptides associated with in vitro assembled brain microtubules, collectively referred to as HMW MAPs (3). NaDodSO4/urea/polyacrylamide gel electrophoresis separates MAP2 into two closely migrating polypeptides, which we designate MAP2a and MAP2b for the slower and faster migrating species, respectively.…”
mentioning
confidence: 99%
“…Bulk separation of MAP 1 from MAP 2 components under non-denaturing conditions revealed that brain MAP 1, like MAP 2, stimulates in vitro polymerization of microtubules (Kuznetzov et al, 1981;Vallee & Davis, 1983). It was also found that lowMr components, referred to as light chains 1-3 (Berkowitz et al, 1977;Vallee & Davis, 1983;Kuznetzov et al, 1986;Kuznetzov & Gelfand, 1987) (Furtner & Wiche 1987). In addition, MAP 1 possesses a binding site for the cytomatrix protein plectin .…”
Section: Other Proceduresmentioning
confidence: 99%